THE IMPACT OF CORPORATE GOVERNANCE ON AUDIT DELAY IN MANUFACTURING COMPANIES - Syifaun Nazla (GREET, 2025)
This study investigates the impact of corporate governance on audit delay in manufacturing companies, a sector where operational complexity and regulatory oversight heighten the importance of timely financial reporting. Using a mixed-method design, quantitative regression analysis was conducted on audit delay and governance data from 50 firms in Greater Jakarta, complemented by thematic insights from interviews with managers, internal auditors, and external auditors. The results demonstrate that effective governance mechanisms—particularly board independence, active audit committees, and strong internal control systems—are significantly associated with reduced audit delays, with firms reporting reductions ranging from 20% to 30% compared to peers with weaker governance structures. Ethical governance practices further foster accountability, minimize financial misreporting, and enhance audit efficiency, while ownership concentration and weak communication between auditors and management are linked to longer audit cycles. These findings extend corporate governance literature by addressing the underexplored dimension of audit timeliness, underscoring that governance effectiveness is not only a matter of regulatory compliance but also a strategic determinant of reporting quality, operational efficiency, and investor confidence. The study offers practical implications for practitioners seeking to strengthen governance frameworks, as well as for policymakers designing regulatory standards that incentivize transparency and accountability in the manufacturing industry.